Production System Development, Aviary and Sliding Turning Product Innovation at CV. Mitra Jaya Company Malang to Increase Sales - Hanafi, Roy; Hidayati, Nur; Farida, Eka (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research was carried out using an R & D (Research and Development) approach or development research that produces a product. By using the ADDIE method (analysis, design, development, implementation and evaluation). This research aims to develop a production system and product innovation. The resulting development products are in the form of development models, 1) Standard Operating Procedures, and 2) Product Innovation. Design/methodology/approach: The model was developed with performance and needs analysis. In the initial development process, researchers consulted and validated with economic experts and IT experts to obtain input and suggestions about the model being developed and to determine the feasibility of the product development model. By using a questionnaire as a research instrument. Findings: The research results obtained from the expert validation test results show that the model score obtained from the economic expert validation test results is (89.28), while the IT expert validation test (85) is in the very good category and does not need revision. In product trials carried out on 15 production employees at CV. Mitra Jaya Company has results with the highest score of 88.25, meanwhile, product innovation was tested on 4 consumers and obtained results with the highest score of 100. Thus, the Standard Operational Procedure development model can be used as a guideline in the production process, while product innovation can be applied to improve old products and new products to increase sales. Paper type: Research Paper